Forced to be rich? returns to compulsory schooling in Britain - Paul J. Devereux; Robert A. Hart (Institute for the Study of Labor (IZA), 2008)
Do students benefit from compulsory schooling? Researchers using changes in compulsory schooling laws as instruments have typically estimated very high returns to additional schooling that are greater than the corresponding OLS estimates and concluded that the group of individuals who are influenced by the law change have particularly high returns to education. That is, the Local Average Treatment Effect (LATE) is larger than the average treatment effect (ATE). However, studies of a 1947 British compulsory schooling law change that impacted about half the relevant population have also found very high instrumental variables returns to schooling (about 15%), suggesting that the ATE of schooling is also very high and higher than OLS estimates suggest. We utilize the New Earnings Survey Panel Data-set (NESPD), that has superior earnings information compared to the datasets previously used and find instrumental variable estimates that are small and much lower than OLS. In fact, there is no evidence of any positive return for women and the return for men is in the 4-7% range. These estimates provide no evidence that the ATE of schooling is very high.
Keywords: J01; 330; Compulsory schooling; return to education; Bildungspolitik; Schule; Schulrecht; Verhaltensökonomik; Bildungsertrag; Großbritannien